Enzymological Basis for Growth Inhibition by l-Phenylalanine in the Cyanobacterium Synechocystis sp. 29108 - Hall, Geraldine C. (1980)
The pattern of allosteric control in the biosynthetic pathway for aromatic amino acids provides a basis to explain vulnerability to growth inhibition by l-phenylalanine (0.2 mM or greater) in the unicellular cyanobacterium Synechocystis sp. 29108. We attribute growth inhibition to the hypersensitivity of 3-deoxy-d-arabinoheptulosonate 7-phosphate synthase to feedback inhibition by l-phenylalanine. Hyperregulation of this initial enzyme of aromatic biosynthesis depletes the supply of precursors needed for biosynthesis of l-tyrosine and l-tryptophan. Consistent with this mechanism is the total reversal of phenylalanine inhibition by a combination of tyrosine and tryptophan. Inhibited cultures also contained decreased levels of phycocyanin pigments, a characteristic previously correlated with amino acid starvation in cyanobacteria. l-Phenylalanine is a potent noncompetitive inhibitor (with both substrates) of 3-deoxy-d-arabinoheptulosonate 7-phosphate synthase, whereas l-tyrosine is a very weak inhibitor. Prephenate dehydratase also displays allosteric sensitivity to phenylalanine (inhibition) and to tyrosine (activation). Both 2-fluoro and 4-fluoro derivatives of phenylalanine were potent analog antimetabolites, and these were used in addition to l-phenylalanine as selective agents for resistant mutants. Mutants were isolated which excreted both phenylalanine and tyrosine, the consequence of an altered 3-deoxy-d-arabinoheptulosonate 7-phosphate synthase no longer sensitive to feedback inhibition. Simultaneous insensitivity to l-tyrosine suggests that l-tyrosine acts as a weak analog mimic of l-phenylalanine at a common binding site. Prephenate dehydratase in the regulatory mutants was unaltered. Surprisingly, in view of the lack of regulation in the tyrosine branchlet of the pathway, such mutants excrete more phenylalanine than tyrosine, indicating that l-tyrosine activation dominates l-phenylalanine inhibition of prephenate dehydratase in vivo. In mutant Phe r19 the loss in allosteric sensitivity of 3-deoxy-d-arabinoheptulosonate 7-phosphate synthase was accompanied by a threefold increase in specific activity. This could suggest that existence of a modest degree of repression control (autogenous) over 3-deoxy-d-arabinoheptulosonate synthase, although other explanations are possible. Specific activities of chorismate mutase, prephenate dehydratase, shikimate/nicotinamide adenine dinucleotide phosphate dehydrogenase, and arogenate/nicotinamide adenine dinucleotide phosphate dehydrogenase in mutant Phe r19 were identical with those of the wild type.